Isolation of AmpC- and extended spectrum β-lactamase-producing Enterobacterales from fresh vegetables in the United States. (February 2022) - Moon, Sun Hee; Udaondo, Zulema; Abram, Kaleb Z.; Li, Xinhui; Yang, Xu; DiCaprio, Erin L.; Jun, Se-Ran; Huang, En
Abstract: Vegetables may serve as a reservoir for antibiotic resistant bacteria and resistance genes. AmpC β-lactamases and extended spectrum beta-lactamases (ESBL) inactivate commonly used β-lactam antibiotics, including penicillins and cephalosporins. In this study, we determined the prevalence of AmpC- and ESBL-producing Enterobacterales in retail vegetables in the United States. A total of 88 vegetable samples were collected for the screening of AmpC and ESBL-producing Enterobacterales using CHROMagar ESBL agar. These vegetables included washed ready-to-eat salad (23), microgreens/sprouts (13), lettuce (11), herbs (11), spinach (5), mushrooms (5), brussels sprouts (4), kale (3), and other vegetable samples (13). AmpC and ESBL activities in these isolates were determined using double disk combination tests. Two vegetable samples (2.27%), organic basil and brussels sprouts, were positive for AmpC-producing Enterobacterales and eight samples (9.09%), including bean sprouts, organic parsley, organic baby spinach, and several mixed salads, were positive for ESBL-producing Enterobacterales . Whole genome sequencing was used to identify the bacterial species and resistance genes in these isolates. Genes encoding AmpC β-lactamases were found in Enterobacter hormaechei strains S43-1 and 74–2, which were consistent with AmpC production phenotypes. Multidrug-resistant E. hormaechei strains S11–1, S17-1, and S45-4 possess an ESBL gene, bla SHV66, whereas five Serratia fonticola isolates contain genes encoding a minor ESBL, FONA-5. In addition, we used shotgun metagenomic sequencing approach to examine the microbiome and resistome profiles of three spinach samples. We found that Pseudomonas was the most prevalent bacteria genus in the spinach samples. Within the Enterobacteriaceae family, Enterobacter was the most abundant genus in the spinach samples. Moreover, antibiotic resistance genes encoding 12 major classes of antibiotics, including β-lactam antibiotics, aminoglycoside, macrolide, fluoroquinolone, and others, were found in these spinach samples. Therefore, vegetables can serve as an important vehicle for transmitting antibiotic resistance. The study highlights the need for antibiotic resistance surveillance in vegetable products. Highlights: Multidrug-resistant ESBL-producing E. hormaechei carrying mcr-9 from vegetables Shotgun metagenomic sequencing revealed a diverse resistome in spinach samples. Antibiotic resistance surveillance is needed for vegetable products.